ARDORA EN EL DESARROLLO DE LA COMPETENCIA 21 QUE CORRESPONDE AL ÁREA DE CyT EN LOS ESTUDIANTES DEL SEGUNDO GRADO DEL NIVEL SECUNDARIA DE LA IE SANTIAGO ANTUNEZ DE MAYOLO CHACHAPOYAS 2023 - Reyna Mori, Wilfredo (2023)
This research, titled "Ardora in the development of the 21st-century competence in the Science and Technology (S&T) area among second-grade students at the 'Santiago Antúnez de Mayolo' High School in Chachapoyas – 2023," aimed to demonstrate to what extent the Ardora software enhances the development of the 21st-century competence in the Science and Technology (S&T) area among second-grade high school students. The research employed a Quantitative research type under the Pre-experimental design, as it involved working with a single group. The study considered a population of 306 students, comprising 193 males and 113 females. A sample of 20 students was selected for the study, with 14 males and 5 females. The research began with a diagnostic phase using a Pre-test, which identified deficiencies in the development of the 21st-century competence in the Science and Technology area. The results showed that 8 students, representing 42%, were at the basic achievement level (C), 10 students, equivalent to 53%, were in the developing stage (B), and 1 student, representing 5%, had achieved proficiency (A) in the evaluated indicators of the dependent variable. Based on the diagnostic results, various activities were designed in Ardora as the primary solution strategy for the identified problem. Following the implementation of this strategy, an evaluation phase was conducted through a Post-test. A comparison between the diagnostic and evaluation moments revealed a significant statistical difference between the Pre-test and Post-test. The results showed that 7 students, representing 37% of the sample, were at the developing stage (B), and 12 students, equivalent to 63%, had achieved proficiency (A). Therefore, it is concluded that the Ardora software has positively influenced and strengthened the development of the targeted competence